Cognitive Performance Among Carriers of Pathogenic Copy Number Variants: Analysis of 152,000 UK Biobank Subjects - Kendall, Kimberley M.; Rees, Elliott; Escott-Price, Valentina; Einon, Mark; Thomas, Rhys; Hewitt, Jonathan; O’Donovan, Michael C.; Owen, Michael J.; Walters, James T.R.; Kirov, George (Biological psychiatry (1969), 2017)
The UK Biobank is a unique resource for biomedical research, with extensive phenotypic and genetic data on half a million adults from the general population. We aimed to examine the effect of neurodevelopmental copy number variants (CNVs) on the cognitive performance of participants. We used Affymetrix Power Tools and PennCNV-Affy software to analyze Affymetrix microarrays of the first 152,728 genotyped individuals. We annotated a list of 93 CNVs and compared their frequencies with control datasets. We analyzed the performance on seven cognitive tests of carriers of 12 CNVs associated with schizophrenia (n = 1087) and of carriers of another 41 neurodevelopmental CNVs (n = 484). The frequencies of the 93 CNVs in the Biobank subjects were remarkably similar to those among 26,628 control subjects from other datasets. Carriers of schizophrenia-associated CNVs and of the group of 41 other neurodevelopmental CNVs had impaired performance on the cognitive tests, with nine of 14 comparisons remaining statistically significant after correction for multiple testing. They also had lower educational and occupational attainment (p values between 10−7 and 10−18). The deficits in cognitive performance were modest (Z score reductions between 0.01 and 0.51), compared with individuals with schizophrenia in the Biobank (Z score reductions between 0.35 and 0.90). This is the largest study on the cognitive phenotypes of CNVs to date. Adult carriers of neurodevelopmental CNVs from the general population have significant cognitive deficits. The UK Biobank will allow unprecedented opportunities for analysis of further phenotypic consequences of CNVs.